The Effect of Rupiah Exchange Rate, Inflation, and Accounting Profit on Stock Returns with GCG as a Moderation Variable - Apriyanto Sinuhaji; Ratih Kusumastuti; Salman Jumaili (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the influence of rupiah exchange rate, inflation, and accounting profit on stock returns simultaneously and partially and to determine good corporate governance to moderate the influence of rupiah exchange rate variables, inflation, and accounting profit on stock returns in manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The research method is a quantitative method that uses secondary data from the annual reports of manufacturing companies in the subsector of the goods and consumption industry. The population of this study is manufacturing companies on the Indonesia Stock Exchange sub-sector of the goods and consumption industry, the sample used was 99 sample observations with 33 companies that were in accordance with the criteria that have been determined through purposive sampling techniques. The analysis tool uses the SPSS 2.7 program using quantitative analysis methods, namely classical assumption test analysis, hypothesis test, and Moderated Regression Analysis (MRA) test. The results of this study show that simultaneously and partially the rupiah exchange rate, inflation, and accounting profit have a significant effect on stock returns, and the variables of good corporate governance are only able to moderate the relationship between accounting profit and stock returns, while the variables of the rupiah exchange rate and inflation are not able to be moderated by the variables of good corporate governance.